Synthetic possibility of polystyrene functionalization based on hydroxyl groups of graphene oxide as nucleophiles. (19th May 2015) - Yu, Rongbing; Zhang, Shupeng; Luo, Yuting; Bai, Ruofei; Zhou, Jiangfang; Song, Haiou
Abstract : The successful wet chemical functionalization of graphene oxide with polystyrene offered the possibility of nucleophilic substitution in heterogeneous phase reactions. Abstract : Rationally designed polystyrene surface-functionalized graphene oxide nanohybrids were synthesized for the first time utilizing the hydroxyl groups in graphene oxide (GO) as nucleophiles. The successful wet chemical functionalization in GO with polystyrene containing phenyl groups offered the possibility of nucleophilic substitution in heterogeneous phase reactions owing to the rigid structure of graphene.